Mechanical properties of sol–gel derived SiO2 nanotubes - Polyakov, Boris; Antsov, Mikk; Vlassov, Sergei; Dorogin, Leonid M; Vahtrus, Mikk; Zabels, Roberts; Lange, Sven; Lõhmus, Rünno (Beilstein Journal of Nanotechnology, 2014)
The mechanical properties of thick-walled SiO2 nanotubes (NTs) prepared by a sol–gel method while using Ag nanowires (NWs) as templates were measured by using different methods. In situ scanning electron microscopy (SEM) cantilever beam bending tests were carried out by using a nanomanipulator equipped with a force sensor in order to investigate plasticity and flexural response of NTs. Nanoindentation and three point bending tests of NTs were performed by atomic force microscopy (AFM) under ambient conditions. Half-suspended and three-point bending tests were processed in the framework of linear elasticity theory. Finite element method simulations were used to extract Young’s modulus values from the nanoindentation data. Finally, the Young’s moduli of SiO2 NTs measured by different methods were compared and discussed.
Keywords: atomic force microscopy (AFM); nanomechanical tests; scanning electron microscopy (SEM); silica nanotubes